'Frankenstein genes', or the Mad Magazine version of the human pseudogenome - Nelson David R (Human Genomics, 2004)
Abstract Annotation of the human genome is inching forward. Seven human chromosomes have now been fully annotated, covering 17 per cent of the genome, and at least one chromosome has been re-annotated. The enormity of the task forces a dependence on automated tools for detecting and assembling the genes, followed by hand curation to correct errors and polish the gene models. The accuracy of gene prediction algorithms is very good for internal exons from intact genes, but these programs do peculiar and exasperating things to pseudogenes. These programs can actually resurrect pseudogenes from the dead, making them into viable gene models for intact proteins, albeit science-fictional proteins. This process is demonstrated for four human pseudogenes from the cytochrome P450 family and one putatively functional P450 gene, CYP2U1, having a non-consensus intron boundary. These examples are offered as a call-to-arms to improve pseudogene prediction as an art in itself, and not as a by-product of gene annotation. Failure to do so will flood the databases with thousands of false-positive predictions. Indeed, they are already there.